Korelasi antara Komunikasi Organisasi dan Budaya Organisasi dengan Iklim Kerja Di Madrasah Tsanawiyah Negeri 1 Bone Sulawesi Selatan - Akram Akram; Susdiyanto Susdiyanto; Muhammad Yaumi (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2019)
This study aims to analyze the correlation between organizational communication and organizational culture with the work climate in MTsN (Islamic junior high school) Bone 1 South Sulawesi both partially and simultaneously. This research is a quantitative research with correlational research design. The instrument used to measure the variables of this study is a questionnaire that has been tested for validity and reliability. Analysis with descriptive statistics and inferential statistics using product moment correlation analysis and multiple correlation with the help of SPSS version 21 software. The results of this study indicate that there is a positive and significant correlation between organizational communication and organizational culture with a work climate in MTsN (Islamic junior high school) 1 Bone Sulawesi Selatan, both partial or simultaneously.